Purchasing Power of Small Commodities Communities - Siska Rahmawati; Isna Fitria Agustina (Indonesian Journal of Public Policy Review, 2022)
The purpose of this study is to describe and analyze Community Empowerment from the ability to buy small commodities in Kedensari Village, Tanggulangin Sidoarjo. This study used descriptive qualitative methods. The data were obtained through observation, documentation, and interviews with the head of Kedensari Village, Kedensari Village Secretary and with Micro,Small And Medium Enterprises actors. Data analysis techniques in this study are data collection, data reduction, data presentation and drawing conclusions. The results showed that the ability to buy small commodities Kedensari Village community was able to buy their daily needs and could help them to support their families. However, there are obstacles, namely that the village government has not been optimal in conducting socialization to the community about the implementation of economic empowerment due to the limited ability of the village government apparatus in conveying information clearly. As well as community involvement and awareness to participate in training organized by the village government in collaboration with local youth organizations is also still lacking.